PENYULUHAN PENINGKATAN KINERJA UMKM DI MASA PANDEMI COVID-19 - Pipie Puspitasari; B Medina Nilasari; Robert Kristaung; Beta Oki Baliartati (Universitas Trisakti, 2022)
The beginning of 2020 was a tough year for all citizens of the world, because the world was hit by the Covid-19 pandemic which paralyzed all aspects of life. The death toll fell, the order of life changed and the macro and micro economy collapsed. This led to many changes to the governance system. Micro, Small and Medium Enterprises (MSMEs) are one of the sectors affected by the COVID-19 pandemic. Even though they are affected by COVID-19, MSMEs must continue to grow. This Community Service (PkM) aims to provide counseling about improving the performance of MSMEs through marketing strategies. The method of implementing PkM is carried out directly through a zoom meeting. The counseling participants were 23 MSME actors assisted by the Insan Palma Sejahtera Foundation in Palmerah - West Jakarta. The results of this counseling can provide knowledge and abilities to participants, and participants also get solutions to their product/service marketing problems during the Covid-19 Pandemic. The results of the questionnaire on the effectiveness of counseling showed that 80% of participants stated that counseling could increase their knowledge and abilities; 80% of participants stated that they had knowledge about how to improve the performance of MSMEs.